Análise sociolinguística da aprendizagem dos clíticos de 3ª pessoa por crianças do 4º ano do ensino fundamental - Vieira Júnior, José Carlos (2012)
Several studies show a continual disuse of clitics 3rd person (lhe, o, a, os, as, and variants) in the form of the oral Brazilian Portuguese (BP), being replaced by the pronoun right, the null object, or by repeating the phrase to they reference. On the other hand, the 3rd person clitics appear commonly in texts written by the media as well as in more formal styles of spoken language, which makes these elements of the programs included in the Portuguese course, in Brazilian schools. This time, this research aims to describe this learning process in terms of linguistic and social, trying to investigate how children interpret the use of these forms - and therefore the standard variety of language - and if and / or as the school promotes the learning of these forms. To answer these questions, we carried out a sociolinguistic research, which analyzes the social and linguistic factors that could influence such learning. To this end, these elements were gradually worked during the school year. Thus, the body of this search is composed of texts and test freely understanding - aimed to verify the understanding of the clitic texts present in infant - and performance - consisting in replacing the clitic appropriate expression. Data were collected in a class of fourth grade of elementary school for 10 months academic, a public school in Belo Horizonte, Minas Gerais, whose students belong to different socioeconomic levels. The results show that: i) the context in which the clitic is inserted contributes significantly to their understanding, ii) with respect to extralinguistic factors, students, whatever their social origin and sex / gender, have difficulty understanding the clitics , however, there is a slight tendency to better use as the favored children of socioeconomic class